2016
DOI: 10.1093/gbe/evw251
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Haploid Chromosome Numbers in the Sunflower Family

Abstract: Chromosome number changes during the evolution of angiosperms are likely to have played a major role in speciation. Their study is of utmost importance, especially now, as a probabilistic model is available to study chromosome evolution within a phylogenetic framework. In the present study, likelihood models of chromosome number evolution were fitted to the largest family of flowering plants, the Asteraceae. Specifically, a phylogenetic supertree of this family was used to reconstruct the ancestral chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…In this work, hypothesized base numbers for each of the 36 main clades were superimposed on the backbone phylogeny provided by [79] and two main patterns of karyotype change emerged, (1) polyploidy is common in Asteraceae and occurs in most major clades and (2) descending dysploid events (in contrast to the rarer increasing dysploidy) are widespread across major lineages. Later on, [80], using explicit models of chromosome evolution, corroborated previous inferences and suggested that karyological evolution has been a very dynamic process in Asteraceae mainly shaped by polyploidy and descending dysploidy scenarios.…”
Section: The Long Evolutionary History Of Asteraceae May Have Erased Phylogenetic Signals Of Itr Sitessupporting
confidence: 74%
See 1 more Smart Citation
“…In this work, hypothesized base numbers for each of the 36 main clades were superimposed on the backbone phylogeny provided by [79] and two main patterns of karyotype change emerged, (1) polyploidy is common in Asteraceae and occurs in most major clades and (2) descending dysploid events (in contrast to the rarer increasing dysploidy) are widespread across major lineages. Later on, [80], using explicit models of chromosome evolution, corroborated previous inferences and suggested that karyological evolution has been a very dynamic process in Asteraceae mainly shaped by polyploidy and descending dysploidy scenarios.…”
Section: The Long Evolutionary History Of Asteraceae May Have Erased Phylogenetic Signals Of Itr Sitessupporting
confidence: 74%
“…Altogether, our data suggest that in Asteraceae the dynamics of ITR formation is too fast or labile to trace the complex karyological evolution that has been hypothesized to occur since the early diversification events in the family [75,80]. Further, part of such lability could be due to other types of karyological changes that erased previous ITR signs inconsistently across lineages.…”
Section: Are Centromeric Itr Signals Remnants Of Dysploidy In Asteraceae?mentioning
confidence: 77%
“…Polyploidy has long been recognised as a frequent mechanism in Asteraceae (Mota et al . and references therein) and the frequency of polyploid species observed for the family, although low for the 1 st approach, was fairly high for the Iberian Peninsula and Andalusia (46.0% and 44.1%, respectively), with genera such has Hieracium L., Leucanthemum Mill., Senecio L., Taraxacum Zinn, Centaurea L. and Artemisia L. having numerous polyploid species.…”
Section: Hybridisation and Polyploidy In The Mediterranean Regionmentioning
confidence: 91%
“…Alternatively, dysploidy events occur primarily at speciation events, and we therefore surmise that these events correspond to increases in diversification. Descending dysploidy is common throughout the evolutionary history of Compositae (Mota & al., 2016). Most notably, the Eurasian Carduus clade has undergone a dramatic dysploidy reduction from n = 11 to n = 8.…”
Section: ■ Discussionmentioning
confidence: 99%